Interpretation of Petrophysical Properties in Reservoir Rock Using Capillary Pressure Data of the Mishrif Formation in West Qurna Oilfield, Southern Iraq - Fatimah Hendi; Amna Handhal (Iraqi Geological Journal, 2023)
In this study, capillary pressure tests for twenty-nine samples acquired from four wells, (Rn-83, WQ-155, WQ286, and WQ-355) were used to estimate pore size distribution, pore-throat sorting, displacement pressure, reservoir grade, oil column, effective porosity, and relative permeability of the Mishrif Formation at West Qurna Oilfield, southern Iraq. Interpretation of capillary pressure data revealed that the formation can be divided into four reservoir facies with different reservoir production performances: very good, good, medium, and poor. The facies with very good performance is characterized by large pore sizes, excellent reservoir grade, low displacement pressure, and high oil saturations. The good facies is characterized by the presence of good pore throat sorting, good reservoir grade, and good porosity. Contrary, Medium-performance reservoir facies are characterized by the presence of medium pore sizes, medium pore throat sorting, and medium reservoir grade. Poorly performing reservoir facies is characterized by small pore size, high displacement pressure, poor throat sorting, and high water saturation levels. Based on the relative permeability calculations some samples are wet with water (water-wet), while others are wet with oil (oil-wet).